Um estudo sobre os diferentes valores modais do verbo 'poder' em entrevistas jornalísticas do espanhol - Rinaldi, Natália [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
This work aims at describing the modal verb poder in Spanish journalistic interviews from the discursive, semantic and syntactic features that involve the verb, in order to verify how epistemic value differs from non-epistemic values. The modality classification adopted was proposed by Hengeveld (2004) and it is the basis for the treatment of modalities within the theoretical model of Functional Discourse Grammar (FDG), functional theory whose architecture follows a top-down operation, i.e. it starts with the speaker's intention and then works down to articulation. The accomplishment of this research, which was realized from a synchronic perspective, seeks to answer the follow questions: i) Which non-epistemic values can poder express in Spanish? ii) Is it possible to considerate poder as an auxiliary verb from the theory of Grammaticalization? iii) Does the construction of poder + infinitive that shows the highest level of grammaticalization correspond to epistemic values or non-epistemic values? iv) What is the relation between the layers in Representational Level and semantic values of epistemic modality and non-epistemic modalities expressed by poder? v) What is the contribution of the context to distinguish epistemic values from non-epistemic values expressed by poder in Spanish? To analyze contextual elements that distinguish from others when epistemic modality is expressed in comparison with non-epistemic modalities, some parameters were chosen, such as presence and features [human] and [animate] of the subject, type of States-of-Affair (SoA), grammatical person of the subject, as well as verbal tense and verbal mode and presence of negation before the modal verb. The corpus of this research consists of 20 journalistic interviews published in the Spanish magazine El País, selected randomly between the years 2000 and 2001, and it belongs to the corpus organized by Gasparini-Bastos (2004). The analysis allows verifying that the ...

Neste trabalho, objetiva-se descrever o verbo modal poder em entrevistas jornalísticas do espanhol a partir dos traços discursivos, semânticos e sintáticos que o envolvem, de modo a verificar em que medida o valor epistêmico diferencia-se dos valores não epistêmicos. A classificação das modalidades adotada foi proposta por Hengeveld (2004) e serve como base para o tratamento das modalidades dentro do modelo teórico da Gramática Discursivo-Funcional (GDF), teoria funcionalista cuja arquitetura segue uma orientação top down, ou seja, parte da intenção do falante para a articulação das formas linguísticas. A realização desta pesquisa, de caráter sincrônico, busca responder às seguintes perguntas: i) Que valores modais não epistêmicos o verbo poder pode expressar no espanhol? ii) O verbo poder pode ser considerado um verbo auxiliar a partir dos conceitos teóricos da Gramaticalização? iii) A construção de poder + infinitivo que apresenta maior grau de gramaticalização corresponde aos valores epistêmicos ou aos não epistêmicos? iv) Qual a relação entre as camadas do Nível Representacional da Gramática Discursivo-Funcional e os valores semânticos de modalidade epistêmica e de modalidades não epistêmicas expressos por poder? v) Qual a contribuição do contexto para a diferenciação dos valores modais epistêmicos e não epistêmicos de poder no espanhol? Para analisar os elementos contextuais que se distinguem na expressão da modalidade epistêmica em comparação às modalidades não epistêmicas, foram selecionados alguns parâmetros de análise, tais como a presença e os traços [humano] e [animado] do sujeito, a natureza do Estado-de-Coisas (EsCo), a pessoa gramatical do sujeito, o tempo e o modo verbal e a presença da negação anteposta ao modal. O córpus de análise utilizado é composto por 20 entrevistas jornalísticas publicadas na revista espanhola El País, selecionadas aleatoriamente entre os...
Keywords: Linguística; Análise linguística (Linguística); Gramática discursivo funcional; Lingua espanhola - Verbos; Lingua espanhola - Modalidade; Lingua espanhola - Escrita; Linguistics